Virtual environment for VR-based stress therapy system design element: User perspective - Zaharuddin F.A.; Ibrahim N.; Yusof A.M.; Rusli M.E.; Mohd Mahidin E.M. (Springer, 2023)
Design; Design elements; Designing factors; Existing systems; Mental stress; User comforts; User perspectives; Virtual reality